Zero-Defects Plug and Play – General Quality Frameworks and Processes for Achieving and Maintaining High Levels of Delivered Product Quality in Computer Manufacturing - Thelin, Jorgen (Jorgen Thelin, 1993)
This Master's dissertation describes the design of the overall quality framework and processes for use in ICL's Ashton Manufacturing plant. It provides a set of generic processes to address the requirement of achieving and maintaining high levels of delivered product quality in a typical high throughput / high mix computer-manufacturing environment. These frameworks are suitably general purpose to be applicable to any similar "world class" manufacturing situation with little alteration. The dissertation outlines the two elements of manufacturing quality, namely conformance (no deviations), and removal of infant mortalities. It shows how Delivered Quality Audits are a key method of assessing the true level of conformance of products shipped to customers, and also of gauging the customer's opinion of total perceived quality. It emphasises the fact the manufacturing must now be regarded as a "knowledge-based" business, where knowledge retention is key to the on-going success of the operation. This is particularly true when viewed against the "fundamental economics of manufacturing", namely the constant need to contain and reduce overhead costs, and which in a climate of recession almost invariably leads to the departure of the oldest and most experienced staff, with a consequent loss of their accumulated knowledge and experiences. The quality processes themselves are shown as interrelated, and unified within a single overall generic framework. The framework is considered as one of the vehicles for obtaining "Loose/Tight fit", where best practice techniques can be prescribed and standardised across the varied product ranges, yet still allowing "customisation" of the generic frameworks to accommodate the beneficial differences of 'Plants within a Plant' The key element of Quality Improvement embodied within the framework is shown to be the generic "corrective action loop", which is capable of handling any of the varied types of problem likely to be encountered within a manufacturing environment. The success of this quality improvement system is critically dependant on the involvement of operations staff and "correction at source". The other key element is the recognition that quality processes and systems have inherent limits to their effectiveness. To be able to exceed these limits, a "breakthrough" or "quantum-leap" change is necessary. While the "breakthrough" activities are being formulated and undertaken to create wide-ranging beneficial change, it is important to recognised that the "control" activities of management are vital to prevent unfavourable changes or reversion to the previous methods occurring. The final key concept explored is the three dimensions of organisational management - accountability, responsibility and authority. The importance of organisational design to align these elements together and match them to the organisational unit boundaries is clear. Ultimately, organisational structure can have a large influence on the operation and effectiveness of the overall quality processes.